1968
DOI: 10.1139/v68-479
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of hexagonal–cubic phase transformation of zinc sulfide in vacuo, in zinc vapor, and in sulfur vapor

Abstract: The kinetics of the hexagonal-cubic phase transformation of zinc sulfide have been studied in vacuo, in zinc vapor, and in sulfur vapor in the temperature range 800-900 "C by a powder X-ray diffraction technique. The transformation rate is enhanced in the presence of sulfur and zinc vapor. In vacuo and in sulfur vapor the reaction is nucleation-controlled with activation energies of 95.0 and 98.5 + 5 kcal, respectively. In zinc vapor the reaction is diffusion-controlled with the diffusion coefficient expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 0 publications
5
31
0
Order By: Relevance
“…An activation energy of 61.5 kcal was obtained by Secco (17) for the lattice diffusion of zinc, that is the movement of zinc through normal zinc sites in the zinc sulfide lattice. A similar value for a lattice diffusion mechanism was given by Bansagi and co-authors (19). The results obtained in the present study are in very good agreement with the activation energy values given by Secco (t7).…”
Section: Discussionsupporting
confidence: 92%
“…An activation energy of 61.5 kcal was obtained by Secco (17) for the lattice diffusion of zinc, that is the movement of zinc through normal zinc sites in the zinc sulfide lattice. A similar value for a lattice diffusion mechanism was given by Bansagi and co-authors (19). The results obtained in the present study are in very good agreement with the activation energy values given by Secco (t7).…”
Section: Discussionsupporting
confidence: 92%
“…Highly consistent linear plots of the above relationships gave (i) E, values of 500 1+-80 kJ/mol for recycled stored samples of K,Na(SO,), and (ii) E, values of 1000 2 150 kJ/mol for freshly prepared individual samples of K,Na(S04)2 and KNaSO, . These high E, values are consistent with activation energy values reported for phase transitions in K2S04 (18), ZnS (15), and anthranilic acid (19 …”
Section: Solid State Kinetics (I) Reaction Between Na2so4 and Ksosupporting
confidence: 89%
“…The degree of hexagonality and extent of crystallographic texture were quantitatively assessed in order to establish their relationship to optical transmission and to provide insight into possible mechanisms for crystallographic transformation during annealing and HIPping. Bansagi et al 40 and Xue and Raj 22 have suggested a simple measure of the degree of hexagonality in polycrystalline ZnS powders and hot-pressed compacts. The degree of hexagonality is determined by measuring the relative atomic fraction of hexagonal stacking or polytypic sequences in a sample.…”
Section: Resultsmentioning
confidence: 99%